A Comprehensive Review on the Role of Medicinal Plants in the Management of Diabetic Wound: A Mechanistic Insight - Saikia, Kalyani; Dutta, Partha Pratim; Aziz Barbhuiya, Sm Abdul (Current Drug Research Reviews, 2025)
<span class=
Keywords: medicinal plants